Effects of land use on environmental conditions and macrophytes in prairie lotic ecosystems - Rosso, Juan Jose (2012)
Fluvial hydrosystems are environments with large landscape to water surface ratio and therefore particularly vulnerable to changes in land use. We analysed the connection of environmental conditions in 31 prairie streams of the Pampa Plain (Argentina) with regional phytogeography and surrounding land use. Furthermore, the relationships between riparian conditions, macrophytes and water physico-chemistry on the reach scale were explored by considering nutrient levels, pH, water conductivity, riparian conditions and the presence of in-stream vegetation cover. Streams draining croplands were characterized by better conservation of the riparian zone, lower pH and higher nitrate than those exposed to cattle intrusion. Unlike surrounding land use, our results revealed that regional phytogeography showed only marginal significant effects on streams. Our results also revealed that a particular combination of environmental variables (poor riparian conditions, high total phosphorous, high pH and low nitrate) was detrimental for the presence of macrophytes. However, the abundance of submersed and emergent macrophytes was not dependent on surrounding land use nor on regional phytogeography.